Detection of tumour necrosis factor alpha in sarcoidosis and tuberculosis granulomas using in situ hybridisation. Issue 5 (May 1994) - Myatt, N; Coghill, G; Morrison, K; Jones, D; Cree, I A
Abstract : AIMS--To determine the site of tumour necrosis factor alpha (TNF alpha) product and mRNA in granulomas. METHOD--In situ hybridisation with digoxigenin labelled or biotinylated oligonucleotide probes was used to demonstrate the presence of total mRNA, and then the presence of TNF alpha mRNA in the biopsy specimens of 37 granulomas (31 sarcoidosis, six tuberculosis). RESULTS--TNF alpha mRNA was detected in epithelioid cells, giant cells, and lymphocytes in the granulomas. Some sarcoidosis specimens did not contain detectable mRNA for TNF, but did contain TNF peptide in the epithelioid or giant cells on immunostaining. This may have been due to stored TNF present in cells in which mRNA for TNF is no longer being produced. CONCLUSION--The results suggest that giant cells should not be regarded as effete cells, as they contain large amounts of mRNA and seem to be actively producing TNF alpha.